A heuristic for designing manufacturing focus units with resource considerations - Sheu, Chwen; Krajewski, Lee J.; Cai, Gangshu (My University, 2012)
This paper presents a model of the plant-within-a-plant (PWP) design problem and demonstrates a heuristic for analyzing the problem. Although the benefits of a manufacturing focus have been articulated in the literature, methods for implementation with consideration for resource requirements have not been developed previously. In this study, we discuss the importance of including resource considerations and propose a methodology that can help managers arrive at a facility design with a high degree of focus and minimum resource needs. A heuristic is developed that incorporates the concept of order-winning criteria and volume into the focus design. The heuristic not only recognizes the effects of conflicting manufacturing tasks, but also considers resource costs and material flows between PWP units. Experimental results show that the proposed methodology offers managers the opportunity to generate and assess alternative PWP designs, which are otherwise unavailable. Overall, this research provides an analytical framework for further research in focused manufacturing.
Keywords: Heuristic; Manufacturing focus units; Plant-within-a-plant design problem; Resource considerations